Microstructure tailoring and thermal stability of directionally solidified Al2O3/GdAlO3 binary eutectic ceramics by laser floating zone melting. Issue 7 (May 2018) - Su, Haijun; Wang, Enyuan; Ren, Qun; Liu, Haifang; Zhao, Di; Fan, Guangyao; Zhang, Jun; Liu, Lin; Fu, Hengzhi
Abstract: Directionally solidified Al2 O3 /GdAlO3 eutectic composite ceramics with low solidification defects are prepared by laser floating zone melting to tailor homogeneous microstructure and thermal stability performance under high temperature gradient. At low solidification rate, the solidification microstructure shows periodical growth striations in which coarse colony microstructure and homogeneous 'Chinese script' irregular eutectic structure are coexisted. The growth striation interval L and solidification rate V follow the relationship of L/V = (238.8 ± 2.4) s. By further optimizing laser processing parameters, the eutectic spacing is greatly refined to submicron scale and microstructure oscillation is eliminated at high solidification rates, and fully regular lamellar/rod eutectic structures are obtained by faceted eutectic transition. The rod-like eutectic spacing ( λ ) and solidification rate ( V ) follow the linear relationship of λ·V 1/2 = 6.21 µm 3/2 s −1/2 . Furthermore, the as-solidified eutectic composite even with fine eutectic structure exhibits excellent thermal stability after heat exposure at 1500 °C for 250 h.